Developing Students' Vocabulary Through Semantic Feature Analysis at the Second Grade Students at SMPN 2 Sungguminasa Gowa - Ratu Yulianti Natsir (-)
The objective of this research is to examine whether or not the use of semantic feature analysis is effective to develop English vocabulary of the second grade students of SMP Negeri 2 Sungguminasa Gowa.This research design was a quasi experimental research. The research conducted at SMP Negeri 2 Sungguminasa Gowa in academic year 2010/2011 with 315 students as a population of the research. The sample of the research was 90 consisted of 45 students as the control class and 45 students as the experimental class selected by cluster random sampling tehnique. The instrument employed in collecting data was vocabulary test. Data was obtained through pretest and posttest for both classes and the result of the test was processed by using SPSS 17.0 version.The result revealed that the application of semantic feature analysis could effective to develop the English vocabulary of the second grade students of SMP Negeri 2 Sungguminasa proved by the mean score of control class in pretest was 58.98 and the mean score of experimental class was 57.64. Whereas, the means score of control class in the posttest was 60.27 which was taught without the aplication semantic feature analysis and the means score of experimental class was 76.09, which was taught semantic feature analysis. The result of t-test was 0.000 or the probability, is less than 0.05 as the level of significance (0.000 0.05). The conclusion based on the result was the application of semantic feature analysis was more effective than teaching withou applying semantic feature analysis in developing English vocabulary for the second grade students of SMP Negeri 2 Sungguminasa Gowa.Keyword : vocabulary, semantic feature, analysis